Multi-primary human-centric lighting based on the optical power ratio and the CCT super-smooth switching algorithms. (15th January 2023) - Zhu, Fangyuan; Lin, Youqin; Huang, Weizhi; Lu, Tingwei; Liu, Zongyuan; Ji, Xiaokun; Kang, Ao; Wang, Huanhua; Chen, Zhong; Wu, Tingzhu
Abstract: The discovery of intrinsically photosensitive retinal ganglion cells related to circadian rhythms has led to an increased research focus on the physiological and psychological effects of artificial lighting sources, with the emerging concept of human-centric lighting. This study tuned the spectra of a six-primary lighting source based on pulse width modulation to obtain the best visual and non-visual performances in work, leisure, and daytime indoor applications. The adopted method uses indicators, including the circadian action factor, goodness-of-fit coefficient, color rendering index, and correlated color temperature (CCT). Among these, a CCT super-smooth switching algorithm has been proposed to achieve the change trajectory of the chromaticity coordinates in the Commission Internationale de L'Eclairage color diagram close to the blackbody radiation curve during the CCT switching process in different cases. Finally, this study can provide useful guidance for improving light qualities and achieving human-centric lighting based on a six-primary lighting source with light-emitting diodes. Highlights: Tunes the spectra of a six-primary lighting source based on the pulse width modulation. Good visual and non-visual effect parameters in work, leisure, and daytime indoor applications are obtained. Numerous optimized points between the initial and the end nodes of CCT and switching CCT slowly. The chromaticity coordinates of CCT nodes are close to the blackbody radiation curve to achieve smooth CCT transitions.